Integrated management of root-knot nematode Meloidogyne javanica (Treub) Chitwood in fennel (Foeniculum vulgare Mill.) - Patel, S K Patel, H V Patel, A D Patel, D J (Journal of Spices and Aromatic Crops, 2005)
Evaluation of organic cakes and nematicides for the management of root-knot nematode (Meloidogyne javanica) on fennel (Foeniculum vulgare) at Kapadvanj (Gujarat) indicated that all the treatments including organic amendments and nematicide either alone or in combination significantly reduced root-knot disease and increased the grain yield over control. Maximum grain yield (2762 kg ha-1) was obtained with the treatment neem cake 1000 kg ha-1 + phorate 1 kg ha-1, which was on par with Neemguard 20 kg ha-1 + phorate 1 kg ha-1 (2566 kg ha-1). Minimum root-knot index (1.64) was recorded in the combined treatment of neem cake 1000 kg ha-1 + phorate 1 kg ha-1, which was on par with castor cake 1000 kg ha-1 + phorate 1 kg ha-1. Maximum net returns (Rs. 22,775 ha-1) was obtained in the treatment neem cake 1000 kg ha-1 + phorate 1 kg ha-1.